Beliefs and Practice of EFL Teachers: Constructivist or Traditional - Sibel Kaymakamoğlu (Informascope, 2014)
This study investigated the EFL teachers' beliefs about the nature of EFL teaching and learning in the Cyprus Turkish State Secondary Schools context to see to what extent their beliefs and perceived classroom practice were compatible with the new curriculum which was based on Constructivist view of learning and teaching. A questionnaire which consisted of  17 items about teachers' beliefs (first part) and 17 corresponding items about teachers' practice (second part) was employed to collect the data. The theoretical foundations of the items were 'EFL Teacher's and Learner's Role', 'Learning Environment', and 'EFL Learning'. In both parts, a 5 point Likert-scale format was used. Frequency distributions, percentages, means and  standard deviations were calculated to provide information about the teachers' beliefs and classroom practice. Two-tailed t-tests were also employed to investigate whether there were any differences between the male and female teachers regarding beliefs and practice.The statistical analysis of the teachers' responses to the questionnaire indicated that the EFL teachers' beliefs and practice, in general, were in line with the new curriculum. The t-test results showed that the male and female teachers' reported perceptions of their beliefs and practice were very similar to each other.